2011
DOI: 10.1111/j.1600-6143.2011.03460.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Window Period Hepatitis-C Infection in High Infectious Risk Donors: Systematic Review and Meta-Analysis

Abstract: The OPTN classifies high infectious risk donors (HRDs) based on criteria originally intended to identify people at risk for HIV infection. These donors are sometimes referred to as 'CDC high risk donors' in reference to the CDC-published guidelines adopted by the OPTN. However, these guidelines are also being used to identify deceased donors at increased risk of window period (WP) hepatitis C virus (HCV) infection, although not designed for this purpose. The actual risk of WP HCV infection in HRDs is unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 70 publications
3
132
0
Order By: Relevance
“…This does not detect individuals in window period, which is much longer for HCV infection, approximately 66 days, due to delayed antibody production [33,34]. Thus, an antibody based detection fails to diagnose the infection during this period.…”
Section: Resultsmentioning
confidence: 99%
“…This does not detect individuals in window period, which is much longer for HCV infection, approximately 66 days, due to delayed antibody production [33,34]. Thus, an antibody based detection fails to diagnose the infection during this period.…”
Section: Resultsmentioning
confidence: 99%
“…For recipients of PHS infectiousrisk kidneys, the estimated rates of HIV transmission are lower than those for HCV. 23,24 By comparison, the annual death rate for wait-listed patients is approximately 4% and higher for subgroups with diabetes or over 60 years of age. 25 Post-transplant patient and allograft survival appear to be similar between recipients of PHS infectious-risk versus standard criteria organs, 26 which is not surprising given the tiny predicted rates of disease transmission.…”
Section: Organ Acceptance and Risks Of Disease Transmissionmentioning
confidence: 99%
“…The PHS is currently working on a revision of these risk factors that should be finalized by late 2012 [13]. A recent metaanalysis demonstrated that for hepatitis C, the highest risk (without NAT screening) of window period infection was 300/10,000 donors for injection drug users [43]. For window period HIV infection, the highest risk was for men who have sex with men (10.2/10,000) and intravenous drug users (12.1/10,000) [44].…”
Section: Increased Risk Deceased Donors and Recipient Follow-upmentioning
confidence: 98%